Psychological security at sport excellence stage - Maidokina, L. G.; Kokurin, A. V.; Kudashkina, O. V.; Treskin, M. Yu. (Theory and Practice of Physical Culture, 2019)
Training systems in modern sports give a special priority to the mental conditioning components that are generally designed to develop a high stress tolerance and facilitate the competitive progress. The growing global competitiveness and the increasingly unfair attitudes of the international sport organizations to the Russian sports require the psychological support service to national athletes being further improved. The national sport elite suffer from the negative attitudes and hostilities on the global sport arenas. The multiple sanctions from the international sport organizations expose the athletes to serious stressors that may undermine their competitive success motivations and athletic spirits. Objective of the study was to analyze requirements to the modern psychological safety systems and test benefits of a new Psychological Safety in Elite Sports system offered by the authors. The study was designed to first test the primary psychological defense in the sample; develop and implement the Psychological Safety in Elite Sports system; and rate the Psychological Safety in Elite Sports benefits by the pre- versus post-experimental tests of the psychological defense and mental controls.